A series of novel Anderson-type polyoxometalate-based MnII complexes constructed from pyridyl-derivatives: assembly, structures, electrochemical and photocatalytic properties. Issue 23 (31st May 2017) - Wang, Xiuli; Sun, Junjun; Lin, Hongyan; Chang, Zhihan; Liu, Guocheng; Wang, Xiang
Abstract : Three novel Anderson-type polyoxometalate-based Mn II complexes were hydrothermally synthesized and structurally characterized. The electrochemical behaviors and photocatalytic activities have been investigated in detail. Abstract : Three novel Anderson-type polyoxometalates (POMs)-based metal–organic complexes (MOCs), namely, [Mn2 (4-pdtz)2 [CrMo6 (OH)5 O19 ](H2 O)4 ] (1 ), {Mn(3-dpye)0.5 [CrMo6 (OH)6 O18 ](H2 O)}·(3-H2 dpye)0.5 (2 ), [Mn2 (3-H2 dpye)(TeMo6 O24 )(H2 O)6 ]·4H2 O (3 ) (4-pdtz = 4-pyridino-bistriazol, 3-dpye = N, N ′-bis(3-pyridinecarboxamide)-1, 2-ethane), were hydrothermally synthesized and structurally characterized by single-crystal X-ray diffraction, IR spectra, powder X-ray diffraction (PXRD) and thermogravimetric analyses (TGA). In complex1, the [CrMo6 (OH)5 O19 ] 4− (CrMo6 ) polyoxoanions bridge the Mn II ions to generate a 1D Mn–CrMo6 inorganic chain, on which the 4-pdtz ligands hang. In2, the adjacent CrMo6 polyoxoanions are linked by Mn II ions to form a 2D inorganic layer, which is further linked by 3-dpye forming a 3D metal–organic framework (POMOF). Interestingly, the large voids of the 3D POMOF accommodate free protonated 3-H2 dpye molecules. In complex3, the adjacent TeMo6 O24 6− (TeMo6 ) polyoxoanions are linked by Mn II ions to form a 1D inorganic chain, the protonated 3-H2 dpye act as bidentate ligands connecting two Mn II centers with the oxygen atoms from amide groups, forming a steady 2D metal organic layer. The effects of various coordination behaviors of the pyridyl-based ligands and central metal ions on the structures of the title complexes have been discussed. The title complexes exhibit excellent electrocatalytic activity towards the reduction of bromate and hydrogen peroxide. In addition, the redox potentials of complex3 is highly sensitive to pH and may be used as a kind of potential pH sensor. The photocatalytic properties of the title complexes under UV and visible irradiation have been investigated in detail.